Detecting the Amount of Eroded and Deposited Sand Using DInSAR - Xiaotao Chang; Jinyun Guo; Xiaoqing Wang (Terrestrial, Atmospheric and Oceanic Sciences, 2011)

(untitled)
DInSAR techniques can be used to monitor changes in desert height due to sandstorms. Hunshandake Sandy Land was used as the test area and was a main source of sand in the vicinity of Beijing. In order to study the source of sandstorm and its impact, a pair of EnviSat ASAR images for January 20 and October 26, 2004 were processed. After the image configuration, flat earth effect correction, data filtering, phase unwrapping and geo-coding, a deformation model over Hunshandake was built. The deformation in the test area ranges from -160 to +120 cm, and the height increased in most areas and decreased in a few locations, which is generally consistent with the sandstorm appearing at Beijing during 2004.